Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Influence of institutional factors on the performance of the agricultural sector in Mozambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Abstract: This paper is a review of the institutions and the performance of the agricultural sector in Mozambique, using an analysis table adapted to the assessment of the connections between the institutions and economic development. In the first part, information is presented on the performance of the sector between 2008 and 2017, showing a per capita reduction in productivity and the production of foodstuffs. The second part offers an analysis on the extent to which, and the way that, the development of the sector institutions influenced agricultural performance during that period. There was found to have been institutional instability that affected performance in the sector, which was unable to slow the reduction in production and productivity, which could reflect a wider socioeconomic and institutional environment, i.e. beyond the agricultural sector. The third part looks at some elements for reflection on institutional issues that could contribute to the debate on the future development of the agricultural sector. We refer to the need to think about the future of agriculture in Mozambique from a long-term perspective, focusing on the adoption and stabilization of an institutional framework aimed at increasing agricultural productivity and preserving the environment.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; institutions / instituições

Influência de Factores Institucionais no Desempenho do Sector Agrário em Moçambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Este artigo constitui uma revisão das instituições e do desempenho do sector agrário em Moçambique, aplicando um quadro de análise adaptado à avaliação da ligação entre as instituições e o desenvolvimento económico. Na primeira parte, apresenta-se informação sobre o desempenho do sector entre 2008 e 2017, verificando-se redução da produtividade e da produção per capita de alimentos. A segunda parte oferece uma análise sobre a medida em que, e o modo como, a evolução das instituições do sector influenciou o desempenho da Agricultura nesse período. Verifica-se ter havido instabilidade institucional que afectou o desempenho do sector, não se tendo logrado travar a redução da produção e da produtividade, o que eventualmente reflecte um ambiente socioeconómico e institucional mais amplo, isto é, além do sector agrário. Na terceira parte, colocam-se alguns elementos de reflexão sobre questões institucionais que possam contribuir para o debate sobre o desenvolvimento futuro do sector agrário. Sugere-se a necessidade de pensar o futuro da Agricultura em Moçambique numa perspectiva de longo prazo, com foco na adopção e estabilização de um quadro institucional orientado para o aumento da produtividade agrária e para a preservação do ambiente.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura; institutions / instituições

Natural resources, institutions, and economic transformation in Mozambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
In the light of Mozambique’s natural resources boom—especially its large-scale investments in mining, oil, and gas—this paper analyses the prospects for the extractive industries to contribute to economic transformation from an institutional perspective. To this purpose, we address the institutional dynamics of the resources sector and consider the underlying causes of the identified outcomes. The National Development Strategy, as the instrument presenting the vision for economic transformation and diversification, is discussed. The paper is based on a desk review—documental and bibliographic—and on primary data gathered by the authors as part of their research into the field of natural resources and the political economy of development. We conclude that, given Mozambique’s political patronage and clientelism, intra-ruling elite competition, limited productive base, weak state capacity, high level of poverty, and recurrent fiscal deficits, the prospects of the current resource boom leading to economic transformation, despite its considerable potential, are at best uncertain.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Recursos naturais, instituições e transformação económica em Moçambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
Face ao boom de recursos naturais em Moçambique — em especial dos seus grandes investimentos em exploração mineira, petróleo e gás —, este documento analisa a perspectiva de as indústrias extractivas contribuírem para a transformação económica de um ponto de vista institucional. Para esse efeito, abordamos a dinâmica institucional do sector dos recursos e consideramos as causas subjacentes aos resultados identificados. É discutida a Estratégia Nacional de Desenvolvimento enquanto instrumento que apresenta a visão para a transformação e diversificação económica. O documento baseia-se numa revisão documental e bibliográfica e em dados primários recolhidos pelos autores no âmbito da sua investigação no campo dos recursos naturais e da economia política do desenvolvimento. Concluímos que, dado o patrocínio político e o clientelismo de Moçambique, a competição no interior da elite governante, a base produtiva limitada, a fraca capacidade do Estado, o elevado nível de pobreza e os défices fiscais recorrentes, as perspectivas de que o actual boom de recursos leve à transformação económica, apesar do seu considerável potencial, são, na melhor das hipóteses, incertas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

‘Goats eat where they are tied up’: illicit and habitual corruption in Mozambique - Tvedten, Inge; Picardo, Rachi (Review of African Political Economy, 2018)
The article shows that corruption is structural and omnipresent in Mozambican society, eﬀectively legitimising corrupt practices at all levels. Using an anthropological approach, it argues that smallscale corruption has the most immediate eﬀects for the urban and rural poor and is so common that it has become an integrated part of daily life, or ‘habitual’. While most of the poor relate to corruption through tacit acceptance and acts of compliance, its practical implications are most severe for the very poorest, who cannot aﬀord to take part in corrupt exchanges and are excluded from vital social relationships and social services. A few case studies included re: Northern Moz.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; corruption / corrupção; institutions / instituições; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Neo-liberal Reforms and Illiberal Consolidations: The Indonesian Paradox - Hadiz, Vedi; Robison, Richard (Journal of Development Studies, 2005)
Market-oriented policy agendas have enjoyed a remarkable influence in Indonesia for almost four decades. Yet, attempts to impose these agendas in any systematic fashion have proven uncertain and inconclusive. This is not simply a case of successful resistance to reform by entrenched interests. Rather, the deepening of market capitalism and global integration has, in many instances, appeared to consolidate authoritarian politics and predatory economic relationships. Even in the wake of economic crisis and dramatic political change, these basic frameworks of power remain largely intact. Such paradoxes raise important questions about the relationships between markets, institutions and political and social power. We examine how market reforms have been resisted and even hijacked to consolidate predatory state and private oligarchies. We look at the way such entrenched interests have been reorganised in the face of fundamental institutional changes, including the collapse of authoritarian rule and the decentralisation of political authority.
Number: 2
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições